Rates and causes of elimination in Malaysia endurance horses - Mohd Rajdi, Nur Zul Izzati; Mohd Adzahan, Noranizan; Adamu, Lawan; Abdullah, Rasedee @ Mat (Cogent OA, 2018)
The performance of endurance horse is usually evaluated on their ability to complete the race successfully. Therefore, the purpose of the present study was to know the current completion and the elimination rate of endurance races in Malaysia. One hundred and ninety-four endurance horses were involved in the present study. All the endurance races were held in the Terengganu International Endurance Park and Az-zahra Arabian Park, Kelantan from May 2015 to August 2016. 35.05% (CI; lower limit = 28.69%, upper limit = 42%) of the horses were eliminated and 64.95% (CI; lower limit = 58%, upper limit = 71.31%) of them were able to complete the race successfully. 54.41% (CI; lower limit = 42.65%, upper limit = 65.69%), 29.41% (CI; lower limit = 19.92%, upper limit = 4.11%) and 16.18% (CI; lower limit = 9.28%, upper limit = 26.69%) of all eliminated horses was due to lameness, metabolic ailments and other reasons respectively. Most of the eliminated horses competed for 80 km while those that completed the race successfully competed in the 40 km race. This data could be of assistance to the Veterinarians in monitoring the trend of endurance races in Malaysia and improve on the current management practices to reduce the rate of elimination in subsequent races.